EKSISTENSI KLAUSUL ARBITRASE DALAM PENENTUAN PENYELESAIAN SENGKETA SYARIAH (Mazahib, 2015)
The absolute authority of religious courts in economics sharia basically can not reach the agreement in which there is a dispute arbitration clause. An arbitration clause in a contract with Islamic principles usually comes first with settlement by means of shura or reconciliation. However, after an attempt made had not yet reached an agreement, the next step is to resolve the dispute the arbitration. In connection with the arbitration clause, the National Sharia Arbitration Board is authorized by law to resolve the dispute among contracting parties on the basis of agreements they have made previously in the contract (arbitration clause). This paper will discuss how the existence of the arbitration clause as limiting the authority of religious courts in handling disputes arising under a contract in the economic field and make sharia arbitration institution designated in the contract has the absolute power to handle dispute resolution sharia. Because the arbitration clause in a contract sharia business is very varied, ability, experience and creativity of businesses and lawyers to formulate an arbitration clause are highly demanded. It is intended that the choice of dispute resolution by means of arbitration actually be achieved more quickly and cost are borne by the parties to the dispute to be lighter.